2021
DOI: 10.21203/rs.3.rs-773379/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Biomonitoring of Bromine-Containing Trihalomethanes in the Pregnant Women: Urinary Levels and Association with Lifestyle Factors

Abstract: Trihalomethanes containing bromine (Br-THMs) are compounds formed from the reaction of organic and inorganic substances in drinking water with chlorine as a common disinfectant. Epidemiological evidence indicated various outcomes as a result of long-term exposure to these compounds. This study aims to investigate the concentration of urinary Br-THMs in a sample of third-trimester pregnant women and to determine its correlation with lifestyle factors. This cross-sectional study was conducted among 118 pregnant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Changes in ambient temperature due to environmental factors can lead to autonomic alterations to maintain core body temperatures within the allocated ranges 16 . Many studies have characterized relationships between weather conditions such as temperature and humidity and pregnancy body response 8 . As gestation age increases, thermoregulatory alterations achieve cold tolerance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in ambient temperature due to environmental factors can lead to autonomic alterations to maintain core body temperatures within the allocated ranges 16 . Many studies have characterized relationships between weather conditions such as temperature and humidity and pregnancy body response 8 . As gestation age increases, thermoregulatory alterations achieve cold tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that weather is associated with short-term mood changes, emotional well-being and behavior changes, and various health conditions: pneumonia, bronchitis, cardiovascular and infectious diseases, stroke, atopic diseases, vitamin D deficiency, changes in sperm count and birth rates, and other morbidity effects 4 4 5 7 . In addition, investigations of weather changes on pregnancy outcomes have examined risks of low birth weight (LBW), preterm birth, gestational diabetes mellitus, preeclampsia, congenital malformations, abortion, and stillbirth 8 . An increase in body temperature in cases of hypothermia have resulted in a decrease in nausea and vomiting symptom in animals, and thermogenic reactions due to cold stress decrease food tolerance and restrain weight loss 9 9 11 .…”
Section: Introductionmentioning
confidence: 99%